Statistical optimization of gelatin immobilization to improve PCL microcarrier surface - Samsudin, Nurhusna; Hashim, Yumi Zuhanis Has-Yun; Arifin, Mohd Azmir; Mel, Maizirwan; Mohd. Salleh, Hamzah; Sopyan, Iis; Jimat, Dzun Noraini (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
Growing cells on microcarriers may have overcome the limitation of conventional cell culture system. However, the main challenge remains at ensuring the surface biocompatibility with cells. Polycaprolactone (PCL), a biodegradable polymer, has received considerable attention because of its excellent mechanical properties and degradation kinetics that suit various applications, but its non-polar hydrocarbon moiety renders it sub-optimal for cell attachment. In this present study, oxygen functional group was introduced via ultraviolet irradiation and ozone aeration (UV/O3) system to allow covalent immobilization of gelatin on the PCL microcarrier surface using zero-length crosslinker reagent 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride and N-hydroxysuccinimide (EDAC/NHS). The optimum conditions for maximizing the amount of gelatin on the surface of PCL were as follows: 1.5 of COOH:EDAC ratio, 10mM NHS concentration and, 80 mg/ml gelatin.